Evaluation of Corrosion Inhibition of 316L Stainless Steel by Permanganate Ions in Chloride Solution - Fahd Arboui; Sid Ahmed Amzert; Mohamed Nadir Boucherit; Salah Hanini; Khaoula Ghezali (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
The efficiency of permanganates to inhibit the scale deposit captured the attention for more investigation on their role as corrosion inhibitor. In this article, the effect of permanganate as corrosion inhibitor on 316L stainless steel in NaCl solution is investigated. The potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) have been performed by varying the electrode stirring speed, the concentration of permanganate ions, pH and the temperature. The results show that the permanganate ions increase the cathodic and anodic currents under effect of stirring speed, due to oxygen reduction reaction and the reduction of permanganate ions. Electrochemical results indicate that the deposit of manganese oxide (MnO2) inhibits the pitting corrosion. The inhibition efficiency is up to 98 % for 10−4 mol.dm−3 of permanganate. The temperature reduces the effectiveness of permanganates against pitting corrosion, the pitting potential shifts cathodically from +0.395 V vs. Saturated Calomel Electrode (SCE) at 298 K to +0.275 V vs. SCE at 343 K. Surface morphology of the deposit oxide films and electrode are studied by emission scanning electron microscopy, X-ray diffraction, Fourier transform infrared and Differential Scanning Calorimetry. The analysis of the deposit layer by X-ray diffraction revealed the presence of δ-MnO2 form, with a crystallite size of 3.17 nm.  Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).